2021
DOI: 10.1155/2021/6660145
|View full text |Cite
|
Sign up to set email alerts
|

Influences on the Seismic Response of the Gravity Dam‐Foundation‐Reservoir System with Different Boundary and Input Models

Abstract: Dynamic dam-foundation interaction is great important in the design and safety assessment of the dam structures. Two classic boundary conditions, i.e., the viscous-spring boundary and the viscous boundary, are employed to consider the radiation damping of the unbounded rock foundation. The input models of seismic excitation of the viscous-spring boundary and the viscous boundary are derived. The accuracy of the two boundary conditions in the dynamic analysis of the dam foundation is verified through the founda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Salamon et al [4] compared the seismic responses of the Pine Flat dam under free-field boundary and non-reflection boundary conditions, and the results showed that the free-field boundary condition was essential to obtain realistic ground motions. Chen et al [20] investigated the influences of two boundary conditions (the viscous-spring boundary and the viscous boundary) in their earthquake input models on the seismic analysis of the Pine Flat and Jin'anqiao gravity dam-foundation-reservoir systems, and the results revealed that the agreement between the two boundary conditions was good. Wang et al [21] investigated the seismic damage development and potential failure pattern of the 142 m high Guandi concrete gravity dam using incremental dynamic analysis (IDA), in which the massless foundation model was used to simulate the damfoundation dynamic interaction, and the truncation boundary of the foundation was set to 1.5 times the dam height in the upstream and downstream directions, and 2 times the dam height in the depth direction.…”
Section: Introductionmentioning
confidence: 99%
“…Salamon et al [4] compared the seismic responses of the Pine Flat dam under free-field boundary and non-reflection boundary conditions, and the results showed that the free-field boundary condition was essential to obtain realistic ground motions. Chen et al [20] investigated the influences of two boundary conditions (the viscous-spring boundary and the viscous boundary) in their earthquake input models on the seismic analysis of the Pine Flat and Jin'anqiao gravity dam-foundation-reservoir systems, and the results revealed that the agreement between the two boundary conditions was good. Wang et al [21] investigated the seismic damage development and potential failure pattern of the 142 m high Guandi concrete gravity dam using incremental dynamic analysis (IDA), in which the massless foundation model was used to simulate the damfoundation dynamic interaction, and the truncation boundary of the foundation was set to 1.5 times the dam height in the upstream and downstream directions, and 2 times the dam height in the depth direction.…”
Section: Introductionmentioning
confidence: 99%
“…is is because for two-dimensional models, the free-field system is a one-dimensional column for both the direct FE method and the analytical method. e analytical method has been used for linear two-dimensional modelling of concrete gravity dams, e.g., by Enzell et al [48] and Chen et al [49].…”
Section: Influence Of the Free-field Modelling Of The Foundation On The Computed Response Of The Dammentioning
confidence: 99%
“…In the design and safety analysis of the dam structures, the dynamic dam-foundation interaction is crucial. Numerous computational techniques, such as rigid, massless, and massed foundation models, have been employed to investigate the dynamic dam-foundation interaction [5,10,16,18,20,21]. Using large foundation models is not necessary, A massless foundation model, in which only the impacts of foundation flexibility are taken into account, was put forth by Clough et al in the 1970s [7].…”
Section: Introductionmentioning
confidence: 99%